Outbreak Investigation Of Food Poisoning At SDN Cibuk Lor and SDN Margoluwih, In Sleman District - Shinta Sumiarsih; Rahman; Baning Rahayujati (Politeknik Karya Persada Muna, 2021)
Baground: On break time around at 09.00 WIB, a dozen students from the State Elementary School (SDN) Cibuk Lor, Sleman allegedly experienced dizziness, nausea and vomiting after eating fried squid snacks sold in around the school area, counted 19 children experienced symptoms of poisoning. The aimed was investigation was carried out on the occurrence of food poisoning, in order to ensure the correctness of the information and determine the risk factors that influence the incidence of food poisoning. Method: Analytical descriptive study using a case control design. With a ratio of 1:2 subjects as many as 108 children. The cases were those who experienced the main symptoms, namely nausea, vomiting and dizziness as 36 children. Data analysis using SPSS 16.0 software and laboratory testing for food samples has been carried out. Results: The average incubation period was 15 minutes, the dominant clinical symptoms were nausea (100%) accompanied by vomiting (16.6%) and dizziness (25%). There are also 2 students who only smell the food but the students also feel dizzy. Fried squid attack rate (66.7%) and no died in this outbreak. The results of laboratory tests showed of Rhodamin and borax in fried squid. Conclusions: Food poisoning occurs due to the use of food mixtures containing hazardous chemicals (rhodamine and borax) and suspected to be contaminated in the food processing. the school and the health center cooperate in tackling the incident by controlling every pitchman comes around the school. Keywords: Outbreak , case control, sleman Pendahuluan: Pada saat jam istirahat sekitar pukul 09.00 WIB, belasan siswa Sekolah Dasar Negeri (SDN) Cibuk Lor, Seyegan, Sleman diduga mengalami pusing, mual dan muntah seusai menyantap jajanan cumi goreng yang dijual di sekitar area sekolah, terhitung 19 anak mengalami gejala keracunan. Tujuan penelitian ini untuk untuk menyelidiki adanya kejadian keracunan makanan, guna memastikan kebenaran informasi dan faktor risiko yang mempengaruhi kejadian keracunan makanan. Metode: Studi deskriptif analitik dilakukan menggunakan desain case control dengan perbandingan 1:2 jumlah subyek sebanyak 108 anak. kasus adalah mereka yang mengalami gejala utama yaitu mual, muntah dan pusing sebanyak 36 anak. analisis data menggunakan software SPSS 16.0 dan untuk sampel makanan telah dilakukan pengujian laboratorium. Hasil: Masa inkubasi rata-rata adalah 15 menit sementara itu gejala klinis yang dominan adalah mual (100%) disertai muntah (16,6%) dan pusing (25%). adapula 2 siswa yang hanya mencium bau makanan akan tetapi siswa tersebut juga merasakan pusing. Attack rate cumi goreng (66,7%) dan tidak ada yang meninggal pada KLB ini. hasil uji laboratorium menunjukkan adanya kandungan Rhodamin dan boraks pada cumi goreng. Kesimpulan: Keracunan makanan terjadi akibat pemakaian bahan campuran makanan yang mengandung bahan kimia berbahaya (rhodamin dan boraks) dan diduga terkontaminasi pada proses pengolahan makanan. Kata kunci: Kejadian luar biasa, case control, sleman